REKOMENDASI PENGELOLAAN KOPI BUBUK PADA HOME INDUSTRY CAP JEMPOL MELALUI PENDAPATAN DI KABUPATEN REJANG LEBONG - Aprianto, Dodi; Herawansyah, Herawansyah; Sitorus, Lizvan M.; Gustian, Meko; Ansiska, Paisal (Jurnal Media Ekonomi (JURMEK), 2021)
Home industry that processes coffee beans into coffee powder is the Cap Jempol household industry where this industry processes coffee beans into ground coffee. The household industry for Cap Jempol is located in Air Bang Village, Curup Tengah District. The home industry has started its business since 1987 processing dry coffee beans into coffee powder. The purpose of this study includes to reveal the amount of revenue and income obtained from the ground coffee business in the Cap Jempol home industry and provide management recommendations to increase income. The type of data used in this research is primary data which is collected through direct interviews with respondents. The results of this study are the business of thumbprint coffee powder management obtains an average profit of Rp. 2,688,116, - per week with an average Boruto income of Rp. 10,201,667, - with a total production cost of Rp. 7,861,884, -. For business development, it can be done by increasing technology-based promotions such as penetrating online markets with more attractive brand design and product packaging, increasing the use of production technology and carrying out quality control on the products produced, increasing business capital, collaborating with sources of innovation in quality improvement. and production quantity.